THE INFLUENCE OF FINANCIAL RATIOS AND GOOD CORPORATE GOVERNANCE TOWARDS FINANCIAL DISTRESS ON ISLAMIC BANKS IN INDONESIA - Nandita Salatifa Diwanti; purwanto . (President University, 2020)
This research aims to empirically prove the influence of debt to total assets ratio, capital adequacy ratio, total assets turnover, return on assets, and good corporate governance towards financial distress by Altman Z-Score. This research uses the population of Islamic banks published in the Financial Service Authority during the period 2013-2018, where the data is collected from official bank websites. Adopting a quantitative research and has 72 observations from 12 banks in six years. The result shows that capital adequacy ratio and return on assets have significant positive influence towards financial distress. While debt to total assets ratio has the significant negative influence to financial distress. However, total assets turnover and good corporate governance have a negative insignificant influence to Financial Distress. Simultaneously, all independent variables have a significant influence on financial distress, which is indicated by a value of 59.9%.